A distributional analysis of the wage gap between Immigrants and Canadian-born workers - Haider, Nasim (Université d'Ottawa | University of Ottawa, 2019)
The findings of this paper reveal a distributional analysis of the wage gap between immigrant and Canadian-born workers, considering socioeconomic characteristics. Wage discrimination has been a topic of interest for decades. In labour economics, marginal productivity determines the wage as a function of labour human capital. This study analyses the wage differences between immigrant and Canadian-born workers in labour market outcomes in order to find the measure of hidden discrimination against immigrants. Using the combined data from the Labour Force Survey (LFS) of the six months’ gap (April 2018 - October 2018), this paper analyses the wage gap among immigrant and Canadian-born workers in the 25-64-year old age group. After applying a standard Oaxaca-Blinder technique and the counterfactual decomposition with distribution regression, the main result reveals the impact on the wage differentials encompassing educational attainment, age, geographical location, marital status and province of residence. A conditional distribution regression with counterfactual distribution is used to measure the percentile impact of immigrants and Canadian-born workers’ wage impact on wage distribution. The results demonstrate that an immigrant earns less than a Canadian-born worker among all age groups and all-educational levels within the 25-64 age group. The wage gap is larger for Canadian-born workers in provinces, cities and industries and occupational groups. Finally, the result compares an Oaxaca decomposition with counterfactual distribution with distribution regression. The findings highlight that earning differentials favour the Canadian-born workers leave immigrants at a disadvantaged. In Oaxaca, education is a positive that is encouraged for immigrants, whereas for Canadian-born workers it is a negative. Conversely, differentials increase until reaching the higher income distribution before declining. Hence, a low level of discrimination occurs in the higher-income groups. This result suggests that if the differential is reduced then labour market productivity could be increased as well as overall worker motivation.